Impact of Globalization, Women’s Empowerment, and Maternal Health in Sub-Saharan Africa (SSA) - Ayenagbo, kossi (Innovation Journal of Social Sciences and Economic Review, 2022)
The purpose of this study is to examine the impact of globalization and women’s empowerment on maternal health in Sub-Saharan Africa. The study utilizes a dynamic panel model applied to a sample of 37 Sub-Saharan African countries, covering the period from 2000 to 2017. For a more granular analysis, the sample is divided into four regional subgroups. The Generalized Method of Moments (GMM) estimator is employed for the overall African context, while the Least Squares Dummy Variable (LSDV) corrected estimator is used for regional analyses. The findings reveal that both foreign direct investment (FDI) and women’s empowerment significantly contribute to reducing maternal mortality rates across Sub-Saharan Africa, with distinct effects observed in the West, East, Central, and Southern regions. These results underscore the multifaceted nature of globalization, which now extends beyond the exchange of goods and services to include technological advancements, migration, and broader impacts across various sectors. The study concludes that enhancing women’s empowerment and attracting FDI are crucial strategies for improving maternal health outcomes in the region. However, the research also highlights the challenges of accurately measuring the impact of service liberalization on health due to data limitations and the complexities of long-term effects. Implications of this study suggest that policymakers should focus on creating an enabling environment for FDI and promoting gender equality initiatives that empower women. Additionally, there is a need for more comprehensive data collection and long-term studies to better understand the enduring effects of globalization on health outcomes.